Assessment of genome complementarity in three beef-on-dairy crossbreds reveals sire-specific effects on production traits with comparable rates of genomic inbreeding reduction - Dorothea Lindtke; Sylvain Lerch; Isabelle Morel; Markus Neuditschko (BMC Genomics)
Abstract Background Crossbreeding beef bulls with dairy cows can improve the economic value and fitness of calves not entering dairy production owing to increased meat yield and heterosis. However, outcrossing might reduce the dosage of alleles that confer local adaptation or result in a higher risk of dystocia due to increased calf size. Given the clear phenotypic differences between beef breeds, the varying phylogenetic distances between beef and dairy breeds, and the genomic variations within breeds, the attainable economic and fitness gains of calves will strongly depend on the selection of sires for crossing. Thus, the aim of this study was to assess genome complementarity between Angus (AAN), Limousin (LIM), or Simmental (SIM) beef bulls and Brown Swiss (BSW) dairy cows by quantifying genomic inbreeding reduction in F1 crosses and identifying genes potentially under BSW-specific selection that might be affected by outcrossing. Results Low-pass sequencing data from 181 cows, 34 bulls, and 301 of their F1 progeny, and body weight and carcass composition measurements of 248 F1s were obtained. The high genomic inbreeding levels detected in the BSW cows were substantially reduced in the crossbreds, with only minor differences between the sire breeds. In the BSW cows, 585 candidate genes under selection were identified, overrepresenting genes associated with milk, meat and carcass, and production traits. Only a few genes were strongly differentiated at nonsynonymous variants between the BSW and beef breeds, including four tightly clustered genes (FAM184B, NCAPG, DCAF16, and LCORL) nearly fixed for alternate alleles in the BSW cows but mostly heterozygous or homozygous for the reference alleles in the AAN and LIM bulls. The alternate allele dosage at these genes significantly correlated with reduced carcass weight and protein mass in F1s. Conclusion Some of the few genes that were highly divergent between the BSW and beef breeds at nonsynonymous variants were likely under strong selection for reduced carcass weight in the BSW breed, potentially due to trade-offs between beef and dairy productions. As alleles with opposing effects still segregate in beef cattle, marker-assisted selection of mating pairs may be used to modulate the desired phenotypes and simultaneously decrease genomic inbreeding.